On the Destructive Role of „mneme” in „ Anonymus Iamblichi” - Narecki, Krzysztof (Collectanea Philologica, 2025)
The article focuses on a passage from the so-called Anonymus Iamblichi (Diels, Kranz 1956: 404) in which the noun μνήμη (“memory”) appears. Contextual philological analysis allows the Author to establish the full semantic scope of mneme and to determine the role it plays in the passage (fragment 7, 25-40) which concerns the lack of respect for the law (lawlessness) and its consequences. Mneme – “the power of remembering” – contributes significantly to the moral downfall of man, which results from the submission to evil. Its evokes mental images (as forms of expression of mneme, most often representing misfortunes), which effectively destroy the psyche and arete – citizen’s virtue; thus leading one to abandoning ethical norms and, consequently, to moral self-destruction. Therefore, mneme has a very negative impact. Although it is undoubtedly an efficient “memory”, it is used for the mental degeneration of an individual, which consequently leads to the destruction of the civic community (polis).